Human Resource Management Practices at Pondok Pesantren Madrasah Tarbiyah Islamiyah Kapau - Basit, abdul (Universitas Islam Negeri (UIN) Mataram, 2024)
Human resource management aimed at enhancing the quality of education at Pondok Pesantren Madrasah Tarbiyah Islamiyah Kapau has generally been implemented. The management of educational financing plays a crucial role in three main areas: First, the economics of education, which relates to overall community spending. Second, school finances, which concern the school’s policies regarding the allocation of funds for student services. Third, the administration of school business taxes, which must be organized directly in alignment with policy objectives. Furthermore, planning in the management of teacher quality improvement at Pondok Pesantren Madrasah Tarbiyah Islamiyah Kapau focuses primarily on formulating clear goals that the institution aims to achieve through strategic planning. The research employed a qualitative approach, utilizing field data to verify emerging theories that were continuously refined throughout the research process.